Effects of nano oxide particles on the growth and photosynthetic characteristics of okra plant under water deficiency - Wang Jiyue; Xu Jiajun; Xie Rongrong; Chen Nian; Yang Mingli; Tian Xiaojian; Shi Denghong (Folia Horticulturae)
Drought, as abiotic stress, has significant detrimental effects on the growth, physiology, yield and nutritional quality of plants. The distinctive characteristics of nanoparticles (NPs) significantly contribute to essential physiological processes, indicating their considerable potential in promoting plant growth. This study investigated the effects of different NPs, including aluminium oxide nanoparticles (ANPs), silica nanoparticles (SNPs) and titanium dioxide nanoparticles (TNPs), on the growth and photosynthesis of okra (Abelmoschus esculentus L.) seedlings under drought stress conditions. The growth characteristics of okra plants were assessed after 48 days of watering. Photosynthetic parameters like photosynthetic rate, transpiration rate, intercellular CO2 concentration (Ci), stomatal conductance and water use efficiency (WUE) were measured with a portable photosynthesis system. The results demonstrated that both ANPs and SNPs can promote the growth and photosynthesis activity of okra plants, with SNPs exhibiting a stronger effect compared to ANPs. The administration of 50 mg · kg−1 SNPs for a defined period demonstrated the most pronounced enhancement in growth and photosynthetic properties. In contrast, TNPs were found to have a significantly harmful influence on the growth and photosynthetic properties of the okra plant. These findings lay an important foundation for assessing the effects of nano oxide particles on okra plants.